2003
DOI: 10.1073/pnas.1136844100
|View full text |Cite
|
Sign up to set email alerts
|

Liquid–vapor oscillations of water in hydrophobic nanopores

Abstract: Water plays a key role in biological membrane transport. In ion channels and water-conducting pores (aquaporins), one-dimensional confinement in conjunction with strong surface effects changes the physical behavior of water. In molecular dynamics simulations of water in short (0.8 nm) hydrophobic pores the water density in the pore fluctuates on a nanosecond time scale. In long simulations (460 ns in total) at pore radii ranging from 0.35 to 1.0 nm we quantify the kinetics of oscillations between a liquid-fill… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

37
396
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 424 publications
(442 citation statements)
references
References 39 publications
(62 reference statements)
37
396
1
Order By: Relevance
“…We noted recent studies on carbon nanotubes showing that water can spontaneously fill small hydrophobic nanopores 36,37 , especially those with small pore diameters [36][37][38][39][40][41][42] , leading to enhanced mass flow or resonance 40,43 . The observed ion conductance of the hydrophobic channel formed by 1a implies that this sub-nm pore may also be filled with water molecules.…”
Section: Direct Measurement Of Transmembrane Water Transportmentioning
confidence: 89%
“…We noted recent studies on carbon nanotubes showing that water can spontaneously fill small hydrophobic nanopores 36,37 , especially those with small pore diameters [36][37][38][39][40][41][42] , leading to enhanced mass flow or resonance 40,43 . The observed ion conductance of the hydrophobic channel formed by 1a implies that this sub-nm pore may also be filled with water molecules.…”
Section: Direct Measurement Of Transmembrane Water Transportmentioning
confidence: 89%
“…The interest in studying such systems arises from the importance of understanding the properties of confined water and from the possibility of extrapolating the conclusions to other physical situations of similar nature, such as water adsorbed in nanopores in biological and geological systems. In recent years, Molecular Dynamics (MD) simulations have been used to study various aspects of these systems in microscopic detail [2,3,4,5,6,7,8]. Such studies complement experimental investigations by providing detailed microscopic understanding of some of the experimentally observed features.…”
Section: Introductionmentioning
confidence: 99%
“…They found that clusters of water molecules are transferred through the nanotube in the form of occasional bursts arising due to pressure fluctuations occurring outside the nanotube. Beckstein et al [3,4] have extended such simulations to 2 study the density fluctuations of water inside other hydrophobic pores. Transport of oxygen and organic molecules such as methane, ethane and ethylene through carbon nanotubes has also been studied [13,14,15,16] through MD simulations.…”
Section: Introductionmentioning
confidence: 99%
“…3 Furthermore, water, which is close to the liquid-vapor transition at normal conditions, can minimize interface area by locally evaporating and forming a 'nanobubble' within hydrophobic confinement. Evidence of bubble formation in confined geometry has been given early by computer simulations of smooth plate-like solutes, 4 but more recently it has been demonstrated in varying degrees in atomistically resolved plate-like solutes, 5,6 hydrophobic tubes and ion channels, 7,8 and in the collapse of proteins, 9,10 suggesting that it plays a key role in the stabilization and folding dynamics of certain classes of biomolecules. 11,12 Experimental evidence of nanobubbles in strong confinement (in contrast to bubbles at a single planar surface 3 ) has been given for instance in studies of water between hydrophobic surfaces, 13 in zeolites and silica nanotubes, 14,15 and on a subnanometer scale in nonpolar protein cavities.…”
Section: Introductionmentioning
confidence: 99%